A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China - Zhang, Da-Peng; Lin, Chen; Yin, Zhan (Zootaxa, 2019)
The genus Haplotropis Saussure, 1888 belongs to family Pamphagidae, superfamily Acridioidea. It contains three species: Haplotropis brunneriana Saussure, 1888; Haplotropis xiai Ye, Shi & Li 2016 and Haplotropis zhuoluensis Ye, Shi & Li 2016 distributed mainly in Amur River region of Asia and China only (Saussure, 1888; Bey-Bienko et Mishchenko, 1951; Otte, 1994; Yin, Shi et Yin, 1996; Storozhenko & Paik, 2011; Yin et al, 2014, Dong et al, 2015; Ye et al, 2016; Zhang et al, 2017; Cigliano et al, 2018). A new species Haplotropis aqiensis sp. nov. is described in this paper. The new species is similar to H. xiai Ye et al., 2016, but differs from latter by tegmina of male extending over the hind margin of first abdominal tergite slightly, length of tegmina 1.7 times width, cover 2/3 tympanum; frontal ridge of male not widened at median ocellus; length interspace of mesosternum in male equal narrowest width; apical half part of cercus suddenly tapering in male and lower margin of epiphallus without projection in the middle. Type specimen is deposited in the College of Plant Protection, Shandong Agricultural University, Taian, Shandong, China.